Validating the measurement model of ai anxiety and UTAUT constructs in faculty knowledge sharing: A PLS-SEM approach - Guangze Yang; Lay, Yoon Fah (Human Resource Management Academic Research Society, 2025)
This pilot study validates the measurement model of AI Anxiety and Unified Theory of Acceptance and Use of Technology (UTAUT) constructs in the context of faculty knowledge-sharing in virtual academic communities. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study assesses the reliability, validity, and factor structure of the adapted scale, rather than conducting a full structural path analysis. Based on a sample of Chinese university faculty members, the results confirm the psychometric robustness of the proposed model, demonstrating high internal consistency, convergent validity, and discriminant validity. The validated scale establishes a solid foundation for future large-scale studies on the role of AI Anxiety in faculty digital engagement. Further research should expand the validation across different cultural contexts and employ full structural path analyses to explore the relationships among AI Anxiety, UTAUT constructs, and faculty technology adoption.